Patterns of musculoskeletal discomforts across sedentary and dynamic working activity types: An occupational health nursing approach - Dr. Ni Luh Dwi Indrayani; Chi-Jane Wang; I Gede Putu Darma Suyasa; Pande Putu Ida Oktaviani; Apiradee Pimsen; Ni Luh Putu Inca Buntari Agustini (Universitas Airlangga, 2026)
Introduction: This study investigated the pattern of musculoskeletal disorders (MDs), including their prevalence and determinants among sedentary and dynamic workers, and analyzed working posture across various job characteristics. Methods: A total of 100 factory workers were recruited for this cross-sectional study. A self-reported Nordic Musculoskeletal Questionnaire was used to confirm the affected body parts, and observational analysis was performed using the Rapid Entire Body Assessment. Descriptive statistics and chi-square (χ²) tests were used. Results: Results showed that 89% of workers reported at least one musculoskeletal symptom in the past 12 months, with discomfort in the neck (52%), lower back (51%), and shoulder (48%) as the most affected regions. Office personnel exhibited higher proportions of discomfort in the wrist (38%), thighs (28%), and ankle and feet (32%) than dynamic workers (p < 0.01). Significant differences across occupational groups were identified in all body regions, with the largest effects in the wrist (χ² = 17.38, p < 0.001), thigh (χ² = 26.53, p < 0.001), and knee (χ² = 11.64, p < 0.01). Female sex (χ² = 4.86, p < 0.05), irregular exercise (χ² = 8.53, p < 0.01), and shorter work duration (χ² = 5.10, p < 0.05) were associated with a higher prevalence of MDs. Conclusions: Dynamic workers exhibited higher ergonomic risk scores, particularly for trunk and leg postures compared to static workers. This study concludes that ergonomic redesign and occupational health nursing interventions based on occupational demands are essential to minimize musculoskeletal disorder risks and promote musculoskeletal well-being.